2022
DOI: 10.1177/03635465221093075
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Iatrogenic Peroneal Nerve Injury in Lateral Meniscal Repair and Safe Zone to Minimize the Risk Based on Actual Arthroscopic Position: An MRI Study

Abstract: Background: Lateral meniscal repair using an all–inside meniscal repair device involves a risk of iatrogenic peroneal nerve injury. To our knowledge, there have been no previous studies evaluating the risk of injury with the knee in the standard operational figure-of-4 position with joint dilatation in arthroscopic lateral meniscal repair. Purpose: To evaluate and compare the risk of peroneal nerve injury and establish the safe and danger zones in repairing the lateral meniscus through the anteromedial, antero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In a study published in 2021, 3 our author group evaluated the risk of posterior neurovascular injuries related to the medial border of the popliteus tendon using preoperative MRIS with the knees in a slightly flexed position and found that there was a risk of injuries when repairing posterior meniscal tissue 19.01 ± 4.67 mm beyond the medial border of the popliteus tendon through the anteromedial portal and 16.53 ± 4.30 mm beyond the medial border of the popliteus tendon through the anterolateral portal. In another study, 2 1 year later, we used MRIS with the knees in the standard arthroscopic position to evaluate the safe and danger zones of repairing lateral meniscal tissue and found that the danger zone was 15.84 ± 4.52 mm beyond the medial border of the popliteus tendon through the anteromedial portal and 9.62 ± 4.60 mm beyond the medial border of the popliteus tendon through the anterolateral portal. However, even though that study 2 evaluated the risk of injuries based on the real-life arthroscopic situation, there was 1 important point of concern: the reference landmark was the medial border of the popliteus tendon, which is quite distant from the posterior meniscus root, leading to a chance of error when applying the results to the actual operative situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study published in 2021, 3 our author group evaluated the risk of posterior neurovascular injuries related to the medial border of the popliteus tendon using preoperative MRIS with the knees in a slightly flexed position and found that there was a risk of injuries when repairing posterior meniscal tissue 19.01 ± 4.67 mm beyond the medial border of the popliteus tendon through the anteromedial portal and 16.53 ± 4.30 mm beyond the medial border of the popliteus tendon through the anterolateral portal. In another study, 2 1 year later, we used MRIS with the knees in the standard arthroscopic position to evaluate the safe and danger zones of repairing lateral meniscal tissue and found that the danger zone was 15.84 ± 4.52 mm beyond the medial border of the popliteus tendon through the anteromedial portal and 9.62 ± 4.60 mm beyond the medial border of the popliteus tendon through the anterolateral portal. However, even though that study 2 evaluated the risk of injuries based on the real-life arthroscopic situation, there was 1 important point of concern: the reference landmark was the medial border of the popliteus tendon, which is quite distant from the posterior meniscus root, leading to a chance of error when applying the results to the actual operative situation.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, 2 1 year later, we used MRIS with the knees in the standard arthroscopic position to evaluate the safe and danger zones of repairing lateral meniscal tissue and found that the danger zone was 15.84 ± 4.52 mm beyond the medial border of the popliteus tendon through the anteromedial portal and 9.62 ± 4.60 mm beyond the medial border of the popliteus tendon through the anterolateral portal. However, even though that study 2 evaluated the risk of injuries based on the real-life arthroscopic situation, there was 1 important point of concern: the reference landmark was the medial border of the popliteus tendon, which is quite distant from the posterior meniscus root, leading to a chance of error when applying the results to the actual operative situation. To decrease this potential risk in the current study, we used the landmark of the lateral border of the posterior LMR to determine the risk of injuries as well as define the safe and danger zones, which are easier to identify and closer to the posterior lateral meniscal tissue than the landmark of the medial border of the popliteus tendon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Axial oblique MRI scans passing through the center of the lateral meniscal tissue were used for the study measurements, with the medial border of the patella chosen as the position of the anteromedial portal and the lateral border of the patella chosen as the anterolateral portal. The risk of iatrogenic peroneal nerve injury was evaluated by drawing a direct line from the anteromedial or anterolateral portal to the medial or lateral border of the popliteus tendon, extending 14 mm beyond the joint capsule, following the recommendations from earlier studies 9,15,16 . The shortest distance was measured from the direct line to the outer border of the peroneal nerve (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, with this technique, there are concerns of potential iatrogenic injury to the peroneal nerve (PN), which is located in close proximity to the lateral joint line in the posterolateral knee compartment [9]. Cadaveric and magnetic resonance imaging (MRI) studies have been conducted to evaluate the risk of injury to the posterolateral neurovascular structures of the knee [1, 4, 7, 8, 12, 14–16, 18, 21, 23, 24, 26]; however, none of these studies focussed on the surgical technique of placing an anchor through the PT or simulated their repairs in knees in the standard arthroscopic lateral meniscal repair position. (see Fig.…”
Section: Introductionmentioning
confidence: 99%